The Matthew Effect: Prevalence of Doctor and Physician Parents among Ophthalmology Applicants - Khair, Diana; Blanchard, Cody C.; Wang, Kevin K.; Moore, Daniel B. (Journal of Academic Ophthalmology, 2023)
Objective This article determines the prevalence of physician parents among ophthalmology residency applications.Design Retrospective, single-center cohort study.Subjects All applicants to the University of Kentucky Ophthalmology Residency between 2018 and 2023.Methods Residency applications were reviewed, with data collection including applicant gender, self-identified Under-Represented in Medicine (URiM) status, United States Medical Licensing Examination (USMLE) Step 1 score, USMLE Step 2 score, and whether the application identified a doctor or physician as a parent. Doctor was defined as a profession requiring a doctorate degree, and similarly, physician as a profession requiring a medical degree.Results A total of 2,057 applications were reviewed, representing 54% of all match participants during the study period. Fourteen percent (296) of applications indicated a parent was a doctor and 12% (253) a parent was a physician. There were no differences between gender, URiM, USMLE Step 1, and Step 2 scores between applicants indicating a doctor or physician as a parent and those that did not (p all > 0.4 and Cohen's d all < 0.02). Of the type of doctors, 85% (253) were physicians, 6% (17) optometrists, 6% (17) Doctors of Philosophy, 3% (8) dentists, 1% (1) pharmacist, and 1% (1) veterinarian. Eighty-six percent (217) of applications with a physician parent provided the type of physician, with ophthalmologist the most common (93, 43%). Ninety-eight percent (249) of applications with a physician parent provided the gender of the parent, with father (168, 68%) more common than mother (42, 17%) or both parents (39, 16%).Conclusion Physician parents are substantially overrepresented in ophthalmology residency applicants. This raises concerns regarding diversity and inclusion efforts for recruitment in medicine.
Keywords: ophthalmology residency; residency application; graduate medical education; recruitment; physician parents; socioeconomic status